Existing challenges and histopathological review of borderline ovarian epithelial tumors - Singh, Richa; Raman, Eva; Agarwal, Preeti; Maurya, Malti Kumari; Jaiswal, Riddhi; Gupta, Sameer; Solanki, Vandana; Agarwal, Shuchi; Singh, Ajay K. (International Journal of Research in Medical Sciences, 2024)
Background: The borderline tumour seen in the ovary can be with or without stromal invasion. Diagnosis and application of the correct criteria are of utmost importance to avoid over or undertreatment of these. We analyzed the borderline tumors reported in 2 years with respect to clinical outcome based on the morphological diagnosis and points that needed reconsideration. Methods: Cases reported as borderline tumors in ovary were retrieved from records reviewed and follow up was recorded. Additionally, we performed a morphometric analysis to confirm the maximum size of the invasive front. Results: A total of 467 resected ovarian tumor specimens were received, of which 266 (266/467 *100=56.9%) were epithelial tumors; out of them 54.88% were benign, 4.88% were borderline and 40.22% were malignant. The mean age at the time of borderline diagnosis was 38.66 years. On follow-up two cases among them developed further disease. One was reported from our center and one from outside, both were mucinous-type tumors. On critical review we found that there was minimal nuclear atypia in both, there was no evidence of convincing stromal invasion except few irregular well formed glands were seen infiltrating the stroma in one case. Conclusions: A large multicenter, interdisciplinary collaboration and data-driven study is needed to reconfirm and reconsider the cut-off of 5mm especially in mucinous tumors.